2020
DOI: 10.1017/s0144686x20000501
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the past, enhancing the present and sharing the future: a qualitative study of the impact of film screenings in care home communities

Abstract: Many care home residents lack opportunities for meaningful activity and social connection, resulting in poor physical and emotional wellbeing. Providing residents with varied activities and social opportunities can improve their quality of life. In this paper, we examine the potential for film to provide a meaningful, social activity. The limited existing research on film in care homes has predominantly examined the use of film clips and materials in stimulating reminiscence for people with dementia. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The reminiscence method is related to the person-centred care model discourse, and an essential part of this method is to refer to the biography of the person with dementia to stimulate them to recall the past ( Breckenridge et al, 2021 ; Rao et al, 2021 ; Saragih et al, 2022 ). Although the participants did not explicitly mention that they adopted or will adopt the reminiscence method in the implementation of TV videos, their sharing showed that they included or will include reminiscence as a part of their implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reminiscence method is related to the person-centred care model discourse, and an essential part of this method is to refer to the biography of the person with dementia to stimulate them to recall the past ( Breckenridge et al, 2021 ; Rao et al, 2021 ; Saragih et al, 2022 ). Although the participants did not explicitly mention that they adopted or will adopt the reminiscence method in the implementation of TV videos, their sharing showed that they included or will include reminiscence as a part of their implementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, they suggested benefits beyond the ones often mentioned in the literature. For example, the literature indicated that TV videos could facilitate self-expression and interaction between people with dementia and healthcare providers ( Bjørnskov et al, 2020 ; Breckenridge et al, 2021 ; Francis et al, 2020 ). Participants talked about these benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature searches, we learned that videos and films could be used with people with major cognitive disorder in different care settings, mainly in long-term care (Bjørnskov et al, 2020;Breckenridge et al, 2021;de Medeiros et al, 2009;Francis et al, 2020;Hall & Hare, 1997;Heller et al, 2009;Loomer et al, 2020;Lundström et al, 2021;Towsley et al, 2021) but also in assisted living (Towsley et al, 2021). There are different types of videos and films used with people with major cognitive disorder in these care settings, mainly videos (Hall & Hare, 1997;Heller et al, 2009;Loomer et al, 2020;Towsley et al, 2021), films/movies (Bjørnskov et al, 2020;Breckenridge et al, 2021;Francis et al, 2020), TV program videos (de Medeiros et al, 2009) but also virtual reality films (Lundström et al, 2021), virtual natural scenery video (Reynolds et al, 2018). Videos and films can be used for different purposes by people with major cognitive disorder, such as recreation (Lundström et al, 2021) and documentation of end-of-life preferences (Towsley et al, 2021).…”
Section: Diverse Uses Of Videos and Films In Care Settingsmentioning
confidence: 99%
“…and cognitive impairment (Breckenridge et al, 2021). Currently, from the literature, TV videos tailored for older adults with dementia are mainly used among English-speaking populations (Bjørnskov et al, 2020;Francis et al, 2020;Breckenridge et al, 2021).…”
mentioning
confidence: 99%